Additional viscous dampers for double-column rocking bridge system: Seismic response and overturning analysis. Issue 141 (February 2021) - Zhou, Yu-Long; Han, Qiang; Du, Xiu-Li; Zhang, Jin-Quan; Cheng, Shou-Shan; Chen, Jing-Yi
Abstract: Rocking systems have proved to be an attractive alternative for seismic resilience under strong earthquakes. In order to investigate the seismic response and overturning of double-column rocking bridge system with viscous dampers (VDs), a multi-block analytical model considering additional VDs is developed in this paper. Compared with the free-rocking system and monolithic system, the seismic response of damped rocking system was analyzed to validate the benefits of VDs for rocking system. The effect of damped system parameters on the seismic response of double-column rocking bridge were also investigated. The analysis illustrates the sensitivity of the overturning to the long distinct pulses of near-field ground motions. Finally, dimensionless overturning spectra for pulse excitations were generated to provide insight into the overturning mechanisms of the damped rocking bridge system and the beneficial effect of viscous dampers on preventing from overturning. Highlights: To develop a multi-block analytical model of double-column rocking bridge systems with viscous dampers. To assess the benefits of viscous dampers to the seismic response of double-column rocking bridge systems. To examine the influence of system parameters on the seismic response of double-column rocking bridge systems. To investigate the effect of viscous dampers on the overturning capacity of double-column rocking bridge systems.